2010
DOI: 10.3892/etm_00000087
|View full text |Cite
|
Sign up to set email alerts
|

Re-assessment of chronic radio-induced tissue damage in a rat hindlimb model

Abstract: Abstract. radiotherapy is successfully used to treat neoplastic lesions, but may adversely affect normal tissues within the irradiated volume. however, additional clinical and para-clinical data are required for a comprehensive understanding of the pathogenesis of this damage. We assessed a rat model using clinical records and medical imaging to gain a better understanding of irradiation-induced tissue damage. the hindlimbs of the rats in this model were irradiated with a single dose of 30 or 50 Gy. Sequential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…In addition, radiation therapy in cancer patients may also lead to irradiating damages to normal tissues [1]. For example, studies have shown that high dose of ionizing irradiation can lead to osteoradionecrosis, loss of bone mass and bone fracture [3,4,33]. Therefore, developing effective radio-protectants is more valuable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, radiation therapy in cancer patients may also lead to irradiating damages to normal tissues [1]. For example, studies have shown that high dose of ionizing irradiation can lead to osteoradionecrosis, loss of bone mass and bone fracture [3,4,33]. Therefore, developing effective radio-protectants is more valuable.…”
Section: Discussionmentioning
confidence: 99%
“…For example, exposure to high-dose ionizing irradiation can cause deleterious effects on bone tissue, and osteoradionecrosis is often seen in cancer patients treated with ionizing irradiation [1,2]. In addition, other serious bone complications, including loss of bone mass, bone fracture and sclerosis, have been reported [3,4]. Increased osteoblastic damage appears to play an important role in the reduced bone mineral density following irradiation [5].…”
Section: Introductionmentioning
confidence: 99%
“…Long after acute phase, radiation-induced osteonecrosis and the dense hypovascular scar left in the radiation bed may leave a poor biologic environment for fusion20). It is well known that high-dose irradiation delivers deleterious effects to bone tissue, including osteoradionecrosis, sclerosis, loss of bone, and bone fracture, in a dose- and time-dependent manner171824). Emery et al6) reported that long bone fractures after irradiation in laboratory animals are associated with a high pseudarthrosis rate, delayed union, decreased strength and decreased periosteal osteoblastic proliferation, decreased formation of cartilage and osteoid, and decreased vascularity after irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, in the patients who underwent interbody fusion perioperative irradiation is known to interfere with bone fusion and to make pseudoarthrosis causing a late fracture after surgery710). The abnormalities observed in the irradiated tissue include the impairment of vascularization due to the high vulnerability of small vascular endothelial cells, impairment of cell homeostasis with cellular apoptosis, and the accumulation of fibrosis18). It is well known that high-dose irradiation delivers deleterious effects to bone tissue, including osteoradionecrosis, sclerosis, loss of bone mass, and bone fracture, in a dose- and time-dependent manner21).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that high-dose irradiation delivers deleterious effects to bone tissue, including osteoradio-necrosis, sclerosis, loss of bone mass, and bone fracture, in a dose-and time-dependent manner. [6][7][8][9] However, the effects of low-dose irradiation on bone responses have rarely been described. Several studies have revealed the detrimental effects of low-dose irradiation (<1 Gy) with various molecular mechanisms, including increases in the generation of reactive oxygen species, DNA double-strand breaks, and chromosomal breakage.…”
mentioning
confidence: 99%